Tindak Pidana Hak Cipta dam Problematika Penegakan Hukumnya - Hanafi Amrani (Fakultas Hukum Universitas Islam Indonesia, 1999)
The protection of the law for the inteilectua! property rights is one form of appreciation to aperson who creates inovative works in the field of scientific and literary artistic works. Indonesia government has aftempled to protect intellectual property rights. By making the law of intelectual property rights, it is expected that violations against the law can be. minimized. In practice, however, the law does not work effectivelly and so infringements continue to develop